The lord of the rings, the two towers [videorecording (DVD)] - Jackson, Peter, 1961-; Wood, Elijah, 1981-; McKellen, Ian; Tyler, Liv; Tolkien, J. R. R. (John Ronald Reuel), 1892-1973 (New Line Home Entertainment, 2003)
Join Frodo, Gandalf, Aragorn, and brave members of the Fellowship as they continue their quest to destroy the Ring of Power. As darkness descends on Middle-earth, a strange creature named Gollum leads the heroes to the Black Gates of Mordor. The rest of Middle-earth prepares for a battle that will decide the fate of all.